The Undiscovered Country: An Analysis of the Nature of the Resurrection in 1 Corinthians 15:35–58. Issue 2 (November 2019) - Cantu, Nathaniel Alejandro
In 1 Corinthians 15:35–58, Paul combats disagreement in the Corinthian church over the nature of the resurrection. Paul's argument for the physicality of the resurrection, and his location of the individual's resurrection within a larger transformation and restoration of all creation, changes how the contemporary church understands and teaches Christian hope, sanctification, and mission.